Analysis Of Factors Affecting Nurse Anxiety Levels In Covid-19 Patients At RSU Royal Prima Medan - Naomi Grace Rezeki; Ermi Girsang; Putranto Manalu (International Journal of Health and Pharmaceutical (IJHP), 2023)
Since the emergence of the first confirmed case of Covid19 in Wuhan at the end of 2019, much attention has been focused on how the patient's health care system to the development of vaccines. However, the discussion about how the struggle of health workers, especially nurses, seems to have received less attention. Therefore, this study was conducted to find out how the anxiety level of nurses for Covid-19 patients is in terms of the influence of organizational support, social support, workload and personal resilience. The results showed that workload and personal resilience had a positive and significant effect on anxiety levels (p < 0.005) but organizational support and social support had no significant effect on anxiety levels (p > 0.005). From the results of the multivariate test, it was found that the p value was 0.000 (p < 0.005) which stated that together or simultaneously, the independent variables in this study had a significant influence on the dependent variable, namely the level of anxiety.